Gross and Biometric Studies on Pelvic Bone of the Emu (Dromaius novaehollandiae - Barvalia, Ishita; Panchal, KM (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The bones of pelvic girdle of emu were studied. The two large os-coxae were less widely separated. No symphysis was found between  two pelvic bones. The fossa renalis was absent. The short pre-acetabular part was in the form of a rough quadrilateral plate, while the  long post-acetabular part was in the form of an elongated triangle. The acetabulum was a deep cavity and perforated. The large ante trochanter was found on caudodorsal part of the acetabulum. The foramen ischiadicum was in the form of a long ilio-ischiatic incisure.  Pubis was a thin rod-like bone directed caudally parallel to the ischium. The large ischio-pubic incisure was divided incompletely into  oval obturator foramen cranially and elongated slit caudally. The gross anatomy of os coxae of emu bird and its biometry have been  described in detail.
Keywords: Avian anatomy; Emu; Gross structure and biometry; Os-coxae; Pelvic limb